RUMAH TANGGA SAKINAH PERSPEKTIF TASAWUF SIMPATIK ( STUDI PADA TAREKAT IDRISIYYAH TASIKMALAYA) - Faiq, Muhammad Nur; Mohamad Hamim; Dedi Ratno (Ahwaluna | Jurnal Hukum Keluarga Islam, 2025)
This research is motivated by the numerous household problems that hinder the realization of a sakinah (tranquil and harmonious) family. These issues include the imbalance and lack of harmony in the mutual relationship between husband and wife, insufficient communication leading to misunderstandings, unstable family economic conditions, external conflicts from the social environment, the loss of family commitment resulting in violence and quarrels, the disappearance of mutual respect that leads to divorce, and various internal and external conflicts that negatively impact family harmony. These problems are viewed as diseases of the heart that cannot be resolved merely through intellectual intelligence but require a spiritual approach through the purification and cleansing of the heart in order to avoid sinful behaviors that can contaminate and close the heart from the truth. The objective of this research is to understand the concept of a sakinah family according to Islamic law and to explore the idea of a sakinah household from the perspective of Sympathetic Sufism within the Idrisiyyah Tariqa. The method used for data observation is qualitative research, as it is relevant to the subject matter, requiring observation, interviews, and document analysis. The approach used is a Theological-Normative one, where Sufi teachings are seen as the esoteric dimension of Islam. The results of this study reveal the presence of serenity, peace, harmony, and love experienced by each family member. The values of Sympathetic Sufism in shaping a sakinah household, particularly within the Idrisiyyah Tariqa, are maintained through consistent spiritual struggle (mujahadah) and discipline (riyadhah). It involves constantly purifying the heart and adorning it with praiseworthy traits. The heart is to be adorned with the attribute of Al-Faqru or spiritual poverty, which in Sufi terminology means a soul that constantly feels in need of Allah SWT. sabr, tawakkul, zuhud, shukr, ridha, and tawadhu. Keywords : Sympathetic Sufism, Sakinah Household, Spiritualist, Idrisiyyah Tariqa, Mujahadah and Riyadhah